Empowering engagement: unveiling motivational drivers for social media adoption: a Facebook case study - Allam, Hesham; Dempere, Juan; Lazaros, Edward J.; Davison, Chris (Frontiers in Computer Science, 2024)
Growingly, social networking websites and applications are manifesting as cultural phenomena.The motivation behind why people in the Middle East utilize social media remains elusive. While numerous examinations have probed how individuals accept and embrace new technology, few have examined how citizens in the UAE take up and employ social media. We put forward and empirically analyze a proposed framework of key aspects that shape users' opinions, objectives, and real usage of social media websites, particularly Facebook, in the UAE, based on the widely acknowledged Technology Acceptance Model. We utilized Structural Equation Modelling and Smart PLS on a sample size of 540 participants and discovered, in addition to the main predictors of Perceived Usefulness and Perceived Ease-of-use , a hedonic dimension including Perceived Enjoyment, Curiosity, and Perceived Connectedness that significantly shape users' attitude towards utilizing Facebook. Further, the findings suggest that Social Presence has a significant connection with users' intention to use Facebook. Our emprical model could spark the emergence of new factors that may influence the uptake of information systems generally, and social media utilities specifically. This research provides backing for the evolution of attitude-behavior theories, shedding light on the reasons behind people's acceptance of dynamic applications.